Visualization for New Generation Users in the Age of the Electronic Book - Green, Peter (33rd Annual IATUL Conference, 2012)
People are visual and respond to images. This is well known and has been exploited for eons by those wishing to sell product and promote ideas. A picture paints a thousand words. Book publishers have taken advantage of the response to images by putting time and effort into book covers. These help to sell the book to the reader. While we may say 'don't judge a book by its cover' in fact we frequently do exactly that. Unfortunately the move to electronic and online in the last decade has diminished the library's ability to take advantage of the visual image of the book when promoting new books to its readers and readers have lost the option to browse the shelf, finding related and useful material by 'chance’. Library users are losing the visual value of real books. However publishers have not stopped creating attractive and informative visual book covers, even for books that are largely sold in the eBook format. People have not changed, they still respond to images and book publishers still wish to make their books attractive to potential readers. At the same time the ability of library clients to consume images has increased remarkably thanks to faster computers, faster networks, mobile devices and smarter graphics. The accelerating transition from paper books to electronic books provides an opportunity and not a threat. Libraries can take the opportunity and provide a traditional service in a new way to our clients and do so in the anytime, anywhere, any-device virtual environment familiar to our new generation users. The library can use its knowledge of its holdings, combined with licensed cover images and clever technology to present a visual experience that replicates the functionality of the paper book. In fact libraries could offer our readers a visualisation experience that we couldn't replicate in the physical world.